Leading a Business School - Julie Davies; Howard Thomas; Eric Cornuel; Rolf D. Cremer (Routledge, 2023)
Business schools are critical players in higher education, educating current and future leaders to make a difference in the world. Yet we know surprisingly little about the leaders of business schools. Leading a Business School demystifies this complex and dynamic role, offering international insights into deans' dilemmas in different contexts and situations. It highlights the importance of deans creating challenging and supportive learning cultures to enhance business and management education, organizations and society more broadly. Written by renowned experts on the role of the dean, Julie Davies, Howard Thomas, Eric Cornuel and Rolf D. Cremer, the book traces the historical evolution of the business school deanship, the current challenges and future sources of disruption. The leadership characteristics and styles of business school deans are presented based on an examination of different dimensions of their roles. These include issues of strategic positioning, such as financial viability, prestige, size, mission, age, location and programme portfolios, as well as the influences of rankings, sector accreditations, governance structures, networks and national policies on strategy implementation. Drawing on international case studies and deans' development programmes globally, the authors explore constraints on deans' autonomy, university and external relations, and how business school deans add value over the period of their tenures. This candid and well-researched book is essential reading for aspiring business school leaders, those hiring and working with deans, and other higher education leaders. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by EFMD Global.
Keywords: 650; Business and Management; Business ethics and social responsibility; Corporate governance: role and responsibilities of boards and directors; Educational administration and organization; Educational strategies and policy